CT measurements of tracheal diameter and length in normocephalic cats. Issue 3 (March 2023) - Zimmermann, Jeannette; Brunner, Anna; Underberg, Julius; Vincenti, Simona
Objectives: The aim of this study was to measure the tracheal dimensions of normocephalic cats using CT. Methods: CT images of 15 client-owned normocephalic cats were retrospectively evaluated to measure the length of the feline trachea. Transverse and vertical inner diameters were measured in five different tracheal regions, and the cross-sectional area of the tracheal lumen was calculated for each point of measurement. Descriptive statistics were applied using a two-tailed t- test. Results: The mean ± SD length of the trachea was 125.13 ± 14.41 mm. Male cats had significantly larger tracheas than female cats. The transverse diameter first increased by 0.94 mm between the most cranial point of measurement and the middle of the trachea. It then decreased by 1.38 mm between the middle of the trachea and the most caudal point of measurement. The vertical diameter decreased by 1.16 mm between the first point of measurement and the penultimate point, and then increased by 0.06 mm between the penultimate point of measurement and the end of the trachea. The two different diameters resulted in an elliptical trachea shape. Conclusions and relevance: The feline trachea was circular only at its cranial and caudal ends, and elliptical with a dorsoventral flattening along the rest of its length. Vertical and transverse diameters varied along the entire length. Tracheal shape differences should be considered when performing permanent tracheostomy, tracheal anastomosis or stenting in cats.